O percurso formativo musical de três professoras: o papel da música na formação inicial e na atuação profissional - Diniz, Juliane Aparecida Ribeiro (2006)
The present research work relates with the musical formation subject of teachers from basic education initial grades and had as objective to discuss and characterize the musical formation of three teachers licensed in pedagogy, emphasizing the initial stage role (graduation course) of this formative passage professional professor. This inquiry methodology was placed in the Qualitative Research scope, approaching the Bibliographical Research, prioritizing the data collection related to the teachers musical formation by halfstructuralized interviews and using the analytical descriptive method for the collected information exposition. The first chapter presents the bibliographical revision on the thematic of the teachers formation in present time, emphasizing the formative passage different stages. The second succinctly delineates the active teachers musical formation working at the initial basic education grades throughout the years, since the Brazilian Normal Schools creation until the current pedagogy courses and, by its end, shows some correlate researches already carried out in the teachers initial musical formation scope, studies that aims at demonstrating how such formations are configured nowadays. The third chapter explicates the methodological ways covered by this study, as well as the interviewed educators profiles. And the last one brings the exposition and discussion of the collected information, which were classified and organized from five analytical categories: Artistic-musical formation in the pre-training phase; Specific musical formation; Initial musical formation; Complementary pedagogicalmusical formation comedy; and Teaching initiation. The data interpretation glimpsed that the initial musical formation is only one of the formative course stages, which supplies the necessary theoretical and methodology bases so that teachers start teaching and search for a permanent and continuous musical formation.